Pembuatan Citrussera Spray Anti Nyamuk Organik Dari Kulit Jeruk dan Serai - Seprianingsih, Dewi; S, Sahratullah; Aulia, Jamiatul; Ulfa, Andi Maria; Novrilianda, Triya (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The use of chemical insecticides as mosquito repellent has the potential to cause negative impacts on health and the environment. Therefore, this study aims to develop Citrussera Spray, an organic mosquito repellent made from orange peel and lemongrass. The content of active compounds such as limonene in orange peel and citronellal in lemongrass have properties as natural repellents. The research method includes extraction of active ingredients using steam distillation and maceration methods, spray formulation, and effectiveness tests on mosquitoes. The results showed that Citrussera Spray has high effectiveness in repelling mosquitoes compared to controls without repellent. In addition, safety tests showed that this product is safe to use without causing skin irritation. Thus, Citrussera Spray can be an innovative alternative as an organic mosquito repellent that is environmentally friendly and safe for health.